Contrived Making Do As Rhetorical Practice in Outdoor Recreation - Senda-Cook, Samantha (Frontiers in Communication, 2017)
Descriptors like “hideous,” “the worst,” “terrible,” and “thrashed” are not the words that most people want to associated with their “usual.” For many outdoor recreators, though, these are things that they learn to live with. But why? Why do they continue to engage in practices that produce these results? I argue that such activities constitute what I call contrived making do and that they function as rhetorical practices that construct identities and parts of the outdoor recreation subculture in three ways: controlling the controllable, walking the edge, and reframing the experience. Contrived making do refers to creating or seeking out situations that necessitate getting by in a physical and/or cultural sense, implying both difficult circumstances and the creativity and wherewithal to figure out improvised solutions. Making do, in this context, depends on privilege, risk—the willingness to take normalized risks and framing risk in culturally expected ways—and voluntarily surrendering some control. This analysis adds nuance and richness to Michel de Certeau’s concept of making do. Whereas de Certeau conceptualized making do as a coping mechanism for marginalized groups, my project illuminates the role that risk plays in making do by showing how a comparatively privileged group of people seek out such experiences. In doing so, this study builds on environmental communication scholarship about risk by demonstrating that mere carelessness may not be the only source of injuries in national parks.